Loading MnO 2-X Chopped carbon fiber-polyacrylonitrile mixed matrix ultrafiltration membrane and preparation method thereof
Through the preparation method of mixed matrix ultrafiltration membrane loaded with MnO2-X chopped carbon fiber and polyacrylonitrile, the problems of poor hydrophilicity and easy pollution of ultrafiltration membrane are solved, and efficient oil-water separation and mechanical performance improvement are achieved.
Patent Information
- Application Number
- CN202411514481.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-29
AI Technical Summary
The existing ultrafiltration membranes have poor hydrophilicity and their prone to contamination and short service life during oil-water separation.
Using the preparation method of MnO2-X chopped carbon fiber-polyacrylonitrile mixed matrix ultrafiltration membrane, the MnO2 nanosheets with oxygen vacancies loaded on chopped carbon fiber were combined with polyacrylonitrile and pore-generating agent for non-unitrile. Ultrafiltration membrane was prepared by solvent phase separation.
It significantly improves the hydrophilicity and oil-water separation performance of the ultrafiltration membrane, enhances the mechanical properties and flux of the membrane, and extends the service life of the membrane.
Smart Images

Figure CN119034499B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ultrafiltration membrane preparation, and in particular to a MnO-loaded 2-X A method for preparing a chopped carbon fiber-polyacrylonitrile mixed matrix ultrafiltration membrane. Background Art
[0002] Ultrafiltration membrane refers to a separation membrane with a pore size between 2-100 nanometers and a molecular weight cutoff greater than 500 Daltons. It has been widely used in oil-water separation, drinking water production and other fields due to its unique separation principle and transmission selectivity, low operating pressure, large flux, small equipment footprint and environmental protection.
[0003] Direct discharges such as oil spills, oilfield produced water, and industrial oily wastewater seriously pollute the ocean, groundwater, and soil. With the deepening of the concept of green, healthy, and sustainable development, the effective treatment of oily wastewater is of great significance to environmental governance, oil recovery, and water recycling. Membrane separation technology has the advantages of high oil removal efficiency and stable water quality, and is one of the most effective methods for treating oily wastewater.
[0004] However, most commercial oil-water separation membranes are polymer membranes and ceramic membranes, some of whose pores are not connected, and the hydrophilicity of the membrane is poor. During the oil-water separation process, oil droplets tend to adhere to the inside of the pores or the surface of the membrane, resulting in a decrease in membrane flux, a decrease in separation efficiency, and a shortened service life. Studies have shown that superhydrophilic modification of the membrane surface can greatly increase the water flux and anti-pollution ability of the membrane. The mechanism is to increase the thickness and density of the hydration layer on the membrane surface and prevent pollutants from contacting the membrane surface.
[0005] Polyacrylonitrile (PAN) has gained more and more attention for its stable structure, stable performance and strong antioxidant properties. It is relatively stable under the action of esters, ketones, alcohols, organic acids (except formic acid) and other commonly used organic solvents. In addition, it has excellent thermal stability and will not melt or soften when heated to above 200°C. At the same time, it has good film-forming properties, simple and controllable preparation, resistance to chemical reagents, high mechanical strength, low cost, and can be reused. It can be used as the first choice for oil-water separation membrane materials. The most special thing is that the polar nitrile group on the PAN chain segment gives it a higher molecular polarity and excellent hydrophilicity. During the operation of the membrane, water molecules tend to quickly gather on the surface of the hydrophilic membrane, further increasing the wettability of the membrane surface, effectively reducing the transmembrane resistance, and greatly alleviating membrane pollution. Based on this, the present invention selects PAN as the preparation material of the ultrafiltration membrane. Summary of the invention
[0006] The present invention provides a MnO-loaded 2-XThe invention discloses a chopped carbon fiber-polyacrylonitrile mixed matrix ultrafiltration membrane and a preparation method thereof, which solves the problems of poor hydrophilicity of the existing ultrafiltration membrane, easy contamination during oil-water separation and short service life.
[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is:
[0008] The present invention provides a MnO-loaded 2-X The method for preparing a chopped carbon fiber-polyacrylonitrile mixed matrix ultrafiltration membrane comprises the following steps:
[0009] Step (1): Add chopped carbon fiber into a beaker containing deionized water, then add potassium permanganate, stir and dissolve for 30 min, and stir and soak at room temperature for 12 h; transfer the mixed solution into a stainless steel reactor, and carry out a sealed constant temperature reaction at 160-200 °C and 300 r / min for 6 h. Filter the product and dry it in vacuum at 60 °C to obtain a loaded MnO 2-X Chopped carbon fiber, chemical reaction formula is shown in formula (1):
[0010]
[0011] Step (2): Add polyacrylonitrile powder into a three-necked flask containing solvent, stir in a constant temperature water bath at 60°C until the polyacrylonitrile powder is completely dissolved, and then add the loaded MnO 2-X The chopped carbon fiber and the porogen are continuously stirred and dispersed to obtain a uniformly mixed casting solution, and the casting solution is placed in a vacuum drying oven at 60°C for 12 h for vacuum degassing;
[0012] Step (3): pour the casting solution slowly onto a clean glass plate at 60°C, scrape it into a liquid film with a film scraper at a constant temperature of 60°C, evaporate it in the air for 20 seconds, and then immerse the glass plate and the liquid film in deionized water at 30°C to cause non-solvent induced phase separation; after the film is completely detached from the glass plate, take it out and soak it repeatedly in deionized water to remove the solvent, and then dry it to obtain the loaded MnO 2-X Chopped carbon fiber-polyacrylonitrile mixed matrix ultrafiltration membrane;
[0013] The porogen is composed of polyethylene glycol 400 and polyethylene glycol 20000 in a mass ratio of (0.5-2):1.
[0014] The thickness of the liquid film is 50 μm, 100 μm, 150 μm, 200 μm or 250 μm.
[0015] The present invention firstly loads MnO2 nanosheets (MnO 2-X ), and then load MnO 2-XThe MnO-loaded carbon fiber was prepared by non-solvent induced phase separation of chopped carbon fiber and PAN. 2-X Chopped carbon fiber-polyacrylonitrile mixed matrix ultrafiltration membrane is applied to oil-water separation.
[0016] MnO2 nanosheets with oxygen vacancy defects (MnO 2-X ) has a large number of defects and oxygen-containing functional groups on its surface, which has a large specific surface area, high activity, easy modification or reaction, and strong hydrophilicity. 2-X Loading onto chopped carbon fibers and then mixing with the PAN membrane substrate can significantly improve the mechanical strength of the mixed matrix ultrafiltration membrane and significantly improve the performance of the membrane.
[0017] Wherein, in step (1), the chopped carbon fiber is a chopped carbon fiber selected from the group consisting of general-purpose polyacrylonitrile-based fiber, viscose-based carbon fiber, asphalt-based carbon fiber, lignin fiber-based carbon fiber, natural fiber-based carbon fiber, recycled fiber-based carbon fiber, and condensed polycyclic aromatic synthetic carbon fiber; the chopped carbon fiber has a diameter of 5-8 μm and a length of less than 20 μm.
[0018] Wherein, in step (1), the specification of potassium permanganate is industrial grade with a purity of >99.5%.
[0019] Wherein, in step (1), the mass volume ratio of the chopped fibers to deionized water is (1-3): 200 g / ml; the mass ratio of the chopped fibers to potassium permanganate is (1.5-2.5): 1.
[0020] Wherein, in step (2), the raw material components in the casting solution are respectively as follows in terms of mass percentage: 2-X Chopped carbon fiber 1-2%, solvent 74-82%, polyacrylonitrile 15-20%, porogen 2-4%.
[0021] Wherein, in step (2), the degree of polymerization of polyacrylonitrile is 1700-1800, and the molecular weight is 140,000-150,000; and the solvent is one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, and N-methylpyrrolidone.
[0022] The present invention also provides a MnO-loaded 2-X The chopped carbon fiber-polyacrylonitrile mixed matrix ultrafiltration membrane is prepared by adopting the above-mentioned preparation method.
[0023] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0024] (1) Chopped carbon fibers were loaded with MnO2 nanosheets (MnO 2-X ), MnO 2-XThe outer surface has abundant oxygen vacancy defects, and its hydrophilicity is stronger than that of MnO2. 2-x It has a layered structure similar to that of nano-sea urchins, which enriches its active sites, achieves superoleophobic properties, and can significantly improve the hydrophilicity and oil-water separation performance of the ultrafiltration membrane.
[0025] (2) OH and MnO in high molecular weight polyethylene glycol (PEG20000) 2-X The main chain of the polymer forms hydrogen bonds with the polyvinyl chloride molecular chain, which improves the compatibility of the organic-inorganic interface. At the same time, the nanochannels formed by the organic-inorganic interface provide additional channels for water penetration, thereby overcoming the trade-off limit and increasing the permeation flux of the membrane.
[0026] (3) PAN polymer matrix encapsulating loaded MnO 2-X Chopped carbon fiber inorganic particles to prevent the loading of MnO 2-X The chopped carbon fibers fall off, and at the same time the introduction of the chopped carbon fibers greatly enhances the mechanical properties of the membrane.
[0027] (4) The mixed matrix ultrafiltration membrane prepared by the present invention has the characteristics of good hydrophilicity, high flux and good oil-water separation effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a scanning electron microscope image of chopped carbon fiber;
[0029] Figure 2 MnO 2-X Scanning electron microscope image of chopped carbon fiber;
[0030] Figure 3 This is a picture of the mixed matrix ultrafiltration membrane of Example 1;
[0031] Figure 4 is a scanning electron microscope cross-sectional view of the film of Example 1;
[0032] Figure 5 This is the oil-water separation effect diagram of Example 1. DETAILED DESCRIPTION
[0033] The technical solution of the present invention will be clearly and completely described below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] In the following examples, the degree of polymerization of polyacrylonitrile is 1700-1800, and the molecular weight is 140,000-150,000; the specification of potassium permanganate is industrial grade with a purity of >99.5%. Example 1
[0035] This embodiment provides a MnO 2-X The method for preparing a chopped carbon fiber-polyacrylonitrile mixed matrix ultrafiltration membrane comprises the following steps:
[0036] (1) Add 30 g of chopped carbon fiber into a beaker containing 2 L of deionized water, then add 15 g of potassium permanganate, stir and dissolve for 30 min, and stir and soak at room temperature for 12 h; transfer the mixed solution to a 5 L stainless steel reactor, seal and react at 160 °C and 300 r / min for 6 h, filter the product, and vacuum dry it at 60 °C to obtain loaded MnO 2-X Chopped carbon fiber. Loaded with MnO 2-X The scanning electron microscope image of carbon nanotubes is shown in Figure 2 shown.
[0037] (2) Add 20 g of polyacrylonitrile powder into a three-necked flask containing 75 g of N,N-dimethylformamide solvent and stir in a constant temperature water bath at 60°C until the polyacrylonitrile powder is completely dissolved. Then add 1 g of loaded MnO 2-X Chopped carbon fiber, 1 g PEG400, 3 g PEG20000 were stirred and dispersed in a constant temperature water bath at 60°C to obtain a uniformly mixed casting solution, and the casting solution was placed in a vacuum drying oven at 60°C for vacuum degassing for 12 h.
[0038] (3) The casting solution was slowly poured onto a clean glass plate at 60°C, and a film was scraped with a constant temperature of 60°C to form a liquid film with a thickness of about 150µm. After evaporation in the air for 20 seconds, the glass plate and the liquid film were completely immersed in deionized water at 30°C. After the film was completely removed from the glass plate, it was taken out and repeatedly soaked in deionized water to remove the solvent. After drying, the loaded MnO was obtained. 2-X Chopped carbon fiber-polyacrylonitrile mixed matrix ultrafiltration membrane. The scanning electron microscope upper surface of the membrane is as follows Figure 3 The scanning electron microscope cross section is shown in Figure 4 shown.
[0039] The diameter of the polyacrylonitrile-based chopped carbon fibers in this embodiment is 5-8 μm and the length is less than 20 μm. The scanning electron microscope image of the chopped carbon fibers is as follows: Figure 1 shown. Example 2
[0040] This embodiment provides a MnO 2-X The method for preparing a chopped carbon fiber-polyacrylonitrile mixed matrix ultrafiltration membrane comprises the following steps:
[0041] (1) Add 20 g of chopped carbon fiber into a beaker containing 2 L of deionized water, then add 13.3 g of potassium permanganate, stir and dissolve for 30 min, and stir and soak at room temperature for 12 h. Transfer the mixed solution to a 5 L stainless steel reactor, seal and react at 180 °C and 300 r / min for 6 h. Filter the product and dry it in vacuum at 60 °C to obtain loaded MnO 2-X Chopped carbon fiber.
[0042] (2) Add 18 g of polyacrylonitrile powder into a three-necked flask containing 76 g of N,N-dimethylacetamide solvent and stir in a constant temperature water bath at 60°C until the polyacrylonitrile powder is completely dissolved. Then add 2 g of loaded MnO 2-X Chopped carbon fiber, 2 g PEG400, and 2 g PEG20000 were stirred and dispersed in a constant temperature water bath at 60°C to obtain a uniformly mixed casting solution, and the casting solution was placed in a vacuum drying oven at 60°C for vacuum degassing for 12 h.
[0043] (3) The casting solution was slowly poured onto a clean glass plate at 60°C, and a film was scraped with a constant temperature of 60°C to form a liquid film with a thickness of about 200 µm. After evaporation in the air for 20 s, the glass plate and the liquid film were completely immersed in deionized water at 30°C. After the film was completely removed from the glass plate, it was taken out and repeatedly soaked in deionized water to remove the solvent. After drying, the loaded MnO was obtained. 2-X Chopped carbon fiber-polyacrylonitrile mixed matrix ultrafiltration membrane.
[0044] The asphalt-based chopped carbon fibers of this embodiment have a diameter of 5-8 μm and a length of less than 20 μm. Example 3
[0045] This embodiment provides a MnO 2-X The method for preparing a chopped carbon fiber-polyacrylonitrile mixed matrix ultrafiltration membrane comprises the following steps:
[0046] (1) Add 10 g of chopped carbon fiber into a beaker containing 2 L of deionized water, then add 4 g of potassium permanganate, stir and dissolve for 30 min, and then stir and soak at room temperature for 12 h. Transfer the mixed solution into a 5 L stainless steel reactor, and keep it in a sealed and constant temperature reactor at 200 °C and 300 r / min for 6 h. Filter the product and dry it in vacuum at 60 °C to obtain the loaded MnO 2-X Chopped carbon fiber.
[0047] (2) Add 20 g of polyacrylonitrile powder into a three-necked flask containing 74 g of dimethyl sulfoxide solvent and stir in a constant temperature water bath at 60°C until the polyacrylonitrile powder is completely dissolved. Then add 2 g of loaded MnO 2-XChopped carbon fiber, 1.5 g PEG400, 2.5 g PEG20000 were stirred and dispersed in a constant temperature water bath at 60°C to obtain a uniformly mixed casting solution, and the casting solution was placed in a vacuum drying oven at 60°C for vacuum degassing for 12 h.
[0048] (3) The casting solution was slowly poured onto a clean glass plate at 60°C, and a film was scraped with a constant temperature of 60°C to form a liquid film with a thickness of about 250 µm. After evaporation in the air for 20 s, the glass plate and the liquid film were completely immersed in deionized water at 30°C. After the film was completely removed from the glass plate, it was taken out and repeatedly soaked in deionized water to remove the solvent. After drying, the loaded MnO was obtained. 2-X Chopped carbon fiber-polyacrylonitrile mixed matrix ultrafiltration membrane.
[0049] The viscose-based chopped carbon fibers of this embodiment have a diameter of 5-8 μm and a length of less than 20 μm. Example 4
[0050] This embodiment provides a MnO 2-X The method for preparing a chopped carbon fiber-polyacrylonitrile mixed matrix ultrafiltration membrane comprises the following steps:
[0051] (1) Add 20 g of chopped carbon fiber into a beaker containing 2 L of deionized water, then add 10 g of potassium permanganate, stir and dissolve for 30 min, and then stir and soak at room temperature for 12 h. Transfer the mixed solution into a 5 L stainless steel reactor, and keep it in a sealed and constant temperature reactor at 160 °C and 300 r / min for 6 h. Filter the product and dry it in vacuum at 60 °C to obtain the loaded MnO 2-X Chopped carbon fiber.
[0052] (2) Add 15 g of polyacrylonitrile powder into a three-necked flask containing 82 g of N-methylpyrrolidone solvent and stir in a constant temperature water bath at 60°C until the polyacrylonitrile powder is completely dissolved. Then add 1 g of loaded MnO 2-X Chopped carbon fiber, 1 g PEG400, and 1 g PEG20000 were stirred and dispersed in a constant temperature water bath at 60°C to obtain a uniformly mixed casting solution, and the casting solution was placed in a vacuum drying oven at 60°C for vacuum degassing for 12 h.
[0053] (3) The casting solution was slowly poured onto a clean glass plate at 60°C, and a film was scraped with a constant temperature of 60°C to form a liquid film with a thickness of about 100 µm. After evaporation in the air for 20 s, the glass plate and the liquid film were completely immersed in deionized water at 30°C. After the film was completely detached from the glass plate, it was taken out and repeatedly soaked in deionized water to remove the solvent. After drying, the loaded MnO was obtained. 2-X Chopped carbon fiber-polyacrylonitrile mixed matrix ultrafiltration membrane.
[0054] The lignin fiber-based chopped carbon fibers of this embodiment have a diameter of 5-8 μm and a length of less than 20 μm.
[0055] Comparative Example 1: 20 g of polyacrylonitrile powder was added to a three-necked flask containing 76 g of N,N-dimethylformamide solvent, and stirred in a constant temperature water bath at 60°C until the polyacrylonitrile powder was completely dissolved, and then 2 g of PEG400 and 2 g of PEG20000 were added in sequence, and the mixture was stirred and dispersed in a constant temperature water bath at 60°C to obtain a uniformly mixed casting liquid, and the casting liquid was placed in a vacuum drying oven at 60°C for vacuum degassing for 12 h. The casting liquid was slowly poured onto a clean 60°C glass plate, and a film was scraped into a liquid film with a thickness of about 200 µm using a constant temperature 60°C film scraper. After evaporation in the air for 20 s, the glass plate and the liquid film were completely immersed in deionized water at 30°C. After the membrane completely fell off the glass plate, it was taken out and repeatedly soaked in deionized water to remove the solvent, and the polyacrylonitrile ultrafiltration membrane was obtained after drying.
[0056] Comparative Example 2: 15 g of polyacrylonitrile powder was added to a three-necked flask containing 82 g of N,N-dimethylacetamide solvent, and stirred in a constant temperature water bath at 60°C until the polyacrylonitrile powder was completely dissolved, and then 1 g of PEG400 and 2 g of PEG20000 were added in sequence, and the mixture was stirred and dispersed in a constant temperature water bath at 60°C to obtain a uniformly mixed casting liquid, and the casting liquid was placed in a vacuum drying oven at 60°C for vacuum degassing for 12 h. The casting liquid was slowly poured onto a clean 60°C glass plate, and a film was scraped into a liquid film with a thickness of about 200 µm using a constant temperature 60°C film scraper. After evaporation in the air for 20 s, the glass plate and the liquid film were completely immersed in deionized water at 30°C. After the membrane was completely detached from the glass plate, it was taken out and repeatedly soaked in deionized water to remove the solvent, and the polyacrylonitrile ultrafiltration membrane was obtained after drying.
[0057] Related tests:
[0058] Determination of pure water flux: Millipore XFUF04701 dead-end filtration ultrafiltration cup with a volume of 90 ml and an effective flow area of 15 cm 2 All membranes were compacted with deionized water at room temperature at 0.15 MPa until the flux was stable. Then, at 0.1 MPa, the volume of deionized water passing through the membrane within 1 min was recorded, and the pure water flux of the membrane was calculated according to formula (2): J 0:
[0059] J 0 =V / (At) (2)
[0060] in, V is the volume of water passing through the membrane, A is the effective area of the membrane, tTo measure time.
[0061] Determination of oil-water separation rate: Replace deionized water with an oil-water mixed emulsion with a mass percentage of 0.1% oil (commercial motor oil), and test the oil retention rate of the membrane after filtering for a period of time at 0.1MPa. R , calculated according to formula (3);
[0062] (3)
[0063] in, C p and C f are the oil concentrations (ppm) in the permeate and feed liquid, respectively. The oil concentration is measured using an SZ-OW online oil concentration meter from Qingdao Jingcheng Instrument Co., Ltd.
[0064] Determination of water flux recovery rate: The ultrafiltration membrane contaminated by oil-water mixture was cleaned with deionized water for 30 min, and then the pure water flux of the ultrafiltration membrane was tested again with deionized water at 0.1 MPa. J 1, then the flux recovery rate of the ultrafiltration membrane FRR, Calculate according to formula (4):
[0065] (4)
[0066] Mechanical properties determination: The mechanical strength of the membrane sample was tested using a universal tensile testing machine. During the test, the dried membrane was cut into rectangular strips of 50 mm × 10 mm (length × width). The tensile rate of the testing machine was 10 mm / min, and the measured value of the mechanical properties was the average of three measurement results.
[0067] The ultrafiltration membranes obtained in Examples 1-4 were tested in comparison with those in Comparative Examples 1-2. The test results are shown in Table 1:
[0068]
[0069] In addition, the oil-water emulsion was filtered using the ultrafiltration membrane obtained in Example 1. Figure 5 As shown, Figure 5 The left side of the figure shows the permeate, and the right side shows the unfiltered oil-water emulsion. Figure 5 It can be seen that the ultrafiltration membrane has good oil-water separation effect.
[0070] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. Loading MnO 2-X The application of chopped carbon fiber-polyacrylonitrile mixed matrix ultrafiltration membrane in oil-water separation is characterized by: The method for preparing the mixed matrix ultrafiltration membrane comprises the following steps: Step (1): Add chopped carbon fiber into a beaker containing deionized water, then add potassium permanganate, stir and dissolve for 30 minutes, and stir and soak at room temperature for 12 hours to obtain a mixed solution. Transfer the mixed solution into a stainless steel reactor, and seal and thermostatically react at 160-200°C and 300 r / min for 6 hours. Filter the product and vacuum dry it at 60°C to obtain loaded MnO 2-X Chopped carbon fiber; Step (2): Add polyacrylonitrile powder into a three-necked flask containing solvent, stir in a constant temperature water bath at 60°C until the polyacrylonitrile powder is completely dissolved, and then add the loaded MnO 2-X The chopped carbon fiber and the porogen are continuously stirred and dispersed to obtain a uniformly mixed casting solution, and the casting solution is placed in a vacuum drying oven at 60° C. for vacuum degassing for 12 hours; Step (3): pour the casting solution slowly onto a clean glass plate at 60°C, scrape it into a liquid film with a film scraper at a constant temperature of 60°C, evaporate it in the air for 20 seconds, and then immerse the glass plate and the liquid film in deionized water at 30°C to cause non-solvent-induced phase separation; after the film is completely detached from the glass plate, take it out and soak it repeatedly in deionized water to remove the solvent, and then dry it to obtain the loaded MnO 2-X Chopped carbon fiber-polyacrylonitrile mixed matrix ultrafiltration membrane; The porogen is composed of polyethylene glycol 400 and polyethylene glycol 20000 in a mass ratio of (0.5-2):1; The thickness of the liquid film is 50 μm, 100 μm, 150 μm, 200 μm or 250 μm; The chopped carbon fiber has a diameter of 5-8 μm and a length of <20 μm; In step (1), the mass volume ratio of the chopped fibers to deionized water is (1-3): 200 g / ml; the mass ratio of the chopped fibers to potassium permanganate is (1.5-2.5): 1; In step (2), the raw material components in the casting solution are respectively as follows in terms of mass percentage: 2-X Chopped carbon fiber 1-2%, solvent 74-82%, polyacrylonitrile 15-20%, porogen 2-4%; The degree of polymerization of the polyacrylonitrile is 1700-1800, and the molecular weight is 140,000-150,000.
2. The use according to claim 1, characterized in that: In step (1), the chopped carbon fiber is one of the general-purpose polyacrylonitrile-based fiber, viscose-based carbon fiber, and asphalt-based carbon fiber.
3. The use according to claim 1, characterized in that: In step (1), the specification of the potassium permanganate is industrial grade with a purity of >99.5%.
4. The use according to claim 1, characterized in that: In step (2), the solvent is one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, and N-methylpyrrolidone.
Citation Information
Patent Citations
Compression-resistant microporous membrane and preparation method thereof
CN103585891A
MnO2-X loaded carbon nanotube-polyvinyl chloride mixed matrix ultrafiltration membrane and preparation method thereof
CN116808843A